2019
DOI: 10.1177/0743915619858939
|View full text |Cite
|
Sign up to set email alerts
|

Older Consumers, Digital Marketing, and Public Policy: A Review and Research Agenda

Abstract: Addressing the challenges created by rapidly aging populations is a topic of intense interest for marketers, policy makers and researchers.However, relatively little research has been undertaken so far into the ways that older consumers are adopting or rejecting new digital technologies. With shifting economic power and growing digital adoption rates amongst older consumers, understanding how they adopt technology and use digital channels is becoming increasingly important to marketers. In order for marketers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 87 publications
2
63
0
2
Order By: Relevance
“…Particularity, shoppers undertake various activities before they make their final purchase decision. This effort may include seeking content from different retailers and asking for social validation of their decision from both their online and offline social networks, which is often out of sight of the actual retailer or brand (Hall et al, 2017;Nunan and Di Domenico, 2019). The empirical evidence indicated that rapid and continued growth in shopper's marketing requires precise communication strategies to drive performance (Hall et al, 2017).…”
Section: Social Media Usage and Its Moderating Role With Customer Satmentioning
confidence: 99%
“…Particularity, shoppers undertake various activities before they make their final purchase decision. This effort may include seeking content from different retailers and asking for social validation of their decision from both their online and offline social networks, which is often out of sight of the actual retailer or brand (Hall et al, 2017;Nunan and Di Domenico, 2019). The empirical evidence indicated that rapid and continued growth in shopper's marketing requires precise communication strategies to drive performance (Hall et al, 2017).…”
Section: Social Media Usage and Its Moderating Role With Customer Satmentioning
confidence: 99%
“…In addition, they draw attention to the great opportunity for scholarship that could meaningfully improve technology-related experiences for elderly populations and the senior market, which is growing substantially with the aging of baby boomers and the increase in life expectancy compared with previous generations. Nunan and Di Domenico (2019) propose that industry and policy makers should be aware of the following aging perspectives: biological/physical, psychological/cognitive, social, and environment/contextual. When firms and governments recognize that technology integration can be useful for each of these perspectives, they can realize important approaches for, or nuances in, treating seniors fairly.…”
Section: Use and Misusementioning
confidence: 99%
“…Parents often embrace the convenience of "sharenting" children's information on social media, unintentionally putting their children at risk (Fox and Hoy 2019). The challenges that older consumers face (Nunan and Di Domenico 2019), such as not being able to plug in or protect their data when connected with technology, place them at risk.…”
Section: Imbalance In a Technology-integrated Societymentioning
confidence: 99%
See 2 more Smart Citations